Effects of Cognitive Remediation on Cognition, Metacognition, and Social Cognition in Patients With Schizophrenia - Montemagni, Cristiana; Del Favero, Elisa; Riccardi, Cecilia; Canta, Laura; Toye, Mario; Zanalda, Enrico; Rocca, Paola (Frontiers in Psychiatry, 2021)
We aimed to evaluate, in a sample of outpatients with schizophrenia (SCZ), the effectiveness of a cognitive remediation (CR) program (through the use of the Cogpack software) (CACR) in addition to standard therapy on cognitive outcomes compared to a control active group (CAG) and to highlight a possible effect on social cognition (SC), metacognition, symptomatology, and real-world functioning. Of the 66 subjects enrolled, 33 were allocated to CACR and 33 to the control active group (CAG). Twenty-three patients in the CACR group and 25 subjects in the CAG completed at least 80% of the 48 prescribed CACR sessions, performed twice a week, for a total of 24 weeks of treatment. A significant time×group interaction was evident, suggesting that patients undergoing CACR intervention improved in positive and negative symptoms, specific cognitive domains (reasoning and problem solving, visual learning, verbal learning), understanding others’ mind, SC, depressive symptoms, awareness of symptoms, and real-world functioning domains (total score, community activities, interpersonal relationships) more significantly than patients undergoing CAG. The most noticeable differential improvement between the two groups were detected in three cognitive domains (reasoning and problem solving, visual learning, and verbal learning) and in depressive symptomatology, with effect sizes ranging from medium to high levels. These are encouraging findings in support of the possible integration of CACR in rehabilitation practice in the Italian mental health services.